Ctrl + Z : the right to be forgotten - Jones, Meg Leta (New York University Press, 2016)
"This is going on your permanent record!" is a threat that has never held more weight than it does in the Internet Age, when information lasts indefinitely. The ability to make good on that threat is as democratized as posting a Tweet or making blog. Data about us is created, shared, collected, analyzed, and processed at an overwhelming scale. The damage caused can be severe, affecting relationships, employment, academic success, and any number of other opportunities--and it can also be long lasting. One possible solution to this threat? A digital right to be forgotten, which would in turn create a legal duty to delete, hide, or anonymize information at the request of another user. The highly controversial right has been criticized as a repugnant affront to principles of expression and access, as unworkable as a technical measure, and as effective as trying to put the cat back in the bag. Ctrl+Z breaks down the debate and provides guidance for a way forward. It argues that the existing perspectives are too limited, offering easy forgetting or none at all. By looking at new theories of privacy and organizing the many potential applications of the right, law and technology scholar Meg Leta Jones offers a set of nuanced choices. To help us choose, she provides a digital information life cycle, reflects on particular legal cultures, and analyzes international interoperability. In the end, the right to be forgotten can be innovative, liberating, and globally viable